2018
DOI: 10.1158/1078-0432.ccr-18-0041
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolism Contributes to Radiation-Induced Immune Checkpoint Reactivation in Glioblastoma

Abstract: Immune checkpoint inhibitors designed to revert tumor-induced immunosuppression have emerged as potent anticancer therapies. Tryptophan metabolism represents an immune checkpoint, and targeting this pathway's rate-limiting enzyme IDO1 is actively being investigated clinically. Here, we studied the intermediary metabolism of tryptophan metabolism in glioblastoma and evaluated the activity of the IDO1 inhibitor GDC-0919, both alone and in combination with radiation (RT). LC/GC-MS and expression profiling was per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 49 publications
2
64
2
1
Order By: Relevance
“…Cysteine and tryptophan metabolism also have established roles in a variety of malignancies, including glioblastoma. 32,33 Our studies reinforce the clear importance that aberrant amino acid metabolism plays in gliomagenesis, with numerous amino acids contributing to diverse metabolic functions enriched in glioblastoma. This included intermediates of serine, glutathione, cysteine, tryptophan, and urea metabolism that have been implicated in many oncogenic roles, including energy production, maintenance of redox balance, protein and nucleotide synthesis, anaplerosis, and immune modulation.…”
Section: Neuro-oncologysupporting
confidence: 70%
“…Cysteine and tryptophan metabolism also have established roles in a variety of malignancies, including glioblastoma. 32,33 Our studies reinforce the clear importance that aberrant amino acid metabolism plays in gliomagenesis, with numerous amino acids contributing to diverse metabolic functions enriched in glioblastoma. This included intermediates of serine, glutathione, cysteine, tryptophan, and urea metabolism that have been implicated in many oncogenic roles, including energy production, maintenance of redox balance, protein and nucleotide synthesis, anaplerosis, and immune modulation.…”
Section: Neuro-oncologysupporting
confidence: 70%
“…50 Although IDO1 inhibitors have not demonstrated antitumor activity as single agents in orthotopic glioma animals, a unique synergy when combined with radiotherapy, temozolomide, or anti-programmed cell death protein 1 antibody has been noted. [28][29][30][51][52][53] TDO inhibitors have not been tested in glioma animals. In this study, RY103, an IDO1/TDO dual inhibitor, showed excellent therapeutic efficacy via downregulating the IDO1/TDO-Kyn-AhR-AQP4 signal pathway in GL261 orthotopic glioma mice.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the work by our group and others in repeatedly demonstrating the remarkable pathogenic influence of IDO in subjects with GBM, the elucidation of its role and multi-variate functions may provide a path for enhancing the effectiveness of cancer immunotherapy against malignant glioma in the future. IDO mRNA is highly expressed in ≥90% of GBM patients presenting with wild-type isocitrate dehydrogenase (wtIDH) and while not normally expressed, is inducible among a majority of human GBM cell lines after exposure to proinflammatory cytokines (23,66,(107)(108)(109)(110). While TDO expression is expressed at an even higher mRNA level than IDO in patient-resected GBM (33,(109)(110)(111), IDO2 levels are negligible or undetectable at the mRNA level (65), despite an IHC-focused study suggesting high IDO2 protein levels in GBM (n = 52) (109); the latter of which likely reflects conclusions based on non-specific antibody immunostaining.…”
Section: Mouse Models For Studying Idomentioning
confidence: 99%
“…long after surgical resection of the tumor which may reflect a treatment-related effect rather than due to the malignancy itself. A recent study by Kesarwani et al provided additional insights into metabolomic profiling of newly diagnosed GBM (n = 80) and lower grade gliomas (LGG, n = 28) demonstrating that, GBM patients have increased intratumoral Trp and Kyn levels, but decreased KA as compared to LGG patients (110). Interestingly, Trp and Kyn accumulation was specific to classical and mesenchymal GBM subtypes, whereas KA accumulation was only evident in the proneural subtype.…”
Section: Mouse Models For Studying Idomentioning
confidence: 99%